The Acoustic Variation of Intonational Correlates in English-Spanish Simultaneous Interpreting - María Lourdes Nafá Waasaf (Miscelánea: A Journal of English and American Studies, 2003)
Intonation is a complex linguistic phenomenon that can be approached acoustically from three main acoustic correlates: fundamental frequency (F0), intensity and duration. This paper analyses the variation of these three correlates in an experimental situation of simultaneous interpreting, focusing the analysis on the degree of monotony of the intonation of the subjects participating in the experiment. It is assumed that language interpreters - as professionals in oral communication - try to reduce the unjustifiably monotonous intonation (in communicative terms) of an original discourse in order to facilitate the reception of the message. The results of this work show that if a speaker presents a speech with a degree of monotony that is unacceptable in communicative terms, the experienced professional interpreter will negatively judge such a mode of delivery and reduce monotony in his or her production. The variation of the three acoustic correlates (F0, intensity and duration) is relative, and must be interpreted with respect to the speaker's usual values (Brown 1977: 127). For this reason, we worked with referential discourses that allowed us to weigh up the increase or reduction of the relative monotony of each subject. The values obtained in this preliminary analysis provided the basis for analysing the degree of monotony in an original speech and two interpretations of the same speech. The original speech was delivered in British English, with monotone intonation, and the two target speeches were delivered in Peninsular Spanish, with non-monotone intonation. In the present work, monotone intonation is defined and characterised - acoustically - by a reduced range, or intonational field, where variations in F0 and intensity are also scarce. Non-monotonous (or melodious) intonation, on the other hand, is characterised by a wider range and more pronounced F0 and intensity inflections. As far as duration is concerned, there does not always seem to be a direct correlation between monotony and speech rate, or duration.
Keywords: intonation; intonational correlates; fundamental frecuency (F0); intensity; duration; simultaneous interpretation; interpreter; original discourse; meta discourse